Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1590/1983-21252018v31n225rc
|View full text |Cite
|
Sign up to set email alerts
|

Use of Treated Sewage as Water and a Nutritional Source for Bean Crops

Abstract: Considering the relevance of the reduction or replacement of fresh water supplies for irrigation, to mitigate the use of agricultural fertilizers and to improve sustainability, this study aimed to evaluate water and nutritional efficiency of treated sewage in cowpea plots. The experiment was conducted in the city of Tianguá-CE, on land belonging to the Water and Sewage Treatment Company of Ceará. It used a randomized block design for the arrangement of split plots. The plots contained two water sources (treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
1
6
0
4
Order By: Relevance
“…Freitas et al [13] employed wastewater in cultivating cowpea (Vigna unguiculata (L.) Walp.) and found a high yield of 935.8 kg ha −1 in treatments irrigated with treated domestic sewage, which was significantly different from the treatments irrigated with well water, 842.4 kg ha −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Freitas et al [13] employed wastewater in cultivating cowpea (Vigna unguiculata (L.) Walp.) and found a high yield of 935.8 kg ha −1 in treatments irrigated with treated domestic sewage, which was significantly different from the treatments irrigated with well water, 842.4 kg ha −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sousa Neto et al [38] found that treated domestic effluent completely replaced mineral fertiliser when growing cotton. Freitas et al [13], growing cowpea (Vigna unguiculata (L.) Walp.) irrigated with treated domestic sewage, pointed out that it can replace commercial fertilisers by up to 100%.…”
Section: Source Of Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Para Freitas et al (2018b) o esgoto doméstico tratado pode substituir em até 100% da nutrição mineral.…”
Section: Introductionunclassified